Comparative chemical profiling, cholinesterase inhibitions and anti-radicals properties of essential oils from Polygonum hydropiper L: A Preliminary anti- Alzheimer's study. Issue 1 (December 2015) - Ayaz, Muhammad; Junaid, Muhammad; Ullah, Farhat; Sadiq, Abdul; Khan, Mir; Ahmad, Waqar; Shah, Muhammad; Imran, Muhammad; Ahmad, Sajjad
Abstract Background Cholinesterase inhibition is a vital target for the development of novel and mechanism based inhibitors, owing to their role in the breakdown of acetylcholine (ACh) neurotransmitter to treat various neurological disorders including Alzheimer's disease (AD). Similarly, free radicals are implicated in the progression of various diseases like neurodegenerative disorders. Due to lipid solubility and potential to easily cross blood brain barrier, this study was designed to investigate the anticholinesterase and antioxidant potentials of the standardized essential oils from the leaves and flowers ofPolygonum hydropiper . Methods Essential oils from the leaves (Ph.LO) and flowers (Ph.FO) ofP. hdropiper were isolated using Clevenger apparatus. Oil samples were analyzed by GC-MS to identify major components and to attribute the antioxidant and anticholinesterase activity to specific components. Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory potentials of the samples were determined following Ellman's assay. Antioxidant assays were performed using 1, 1-diphenyl, 2-picrylhydrazyl (DPPH), 2, 2-azinobis[3-ethylbenzthiazoline]-6-sulfonic acid (ABTS) and hydrogen peroxide (H2 O2 ) free radical scavenging assays. Results In the GC-MS analysis 141 and 122 compounds were indentified in Ph.LO and Ph.FO respectively. Caryophylene oxide (41.42 %) was the major component in Ph.FO while decahydronaphthalene (38.29 %) was prominent in Ph.LO. In AChE inhibition, Ph.LO and Ph.FO exhibited 87.00** and 79.66***% inhibitions at 1000 μg/ml with IC50 of 120 and 220 μg/ml respectively. The IC50 value for galanthamine was 15 μg/ml. In BChE inhibitory assay, Ph.LO and Ph.FO caused 82.66*** (IC50 130 μg/ml) and 77.50***% (IC50 225 μg/ml) inhibitions respectively at 1000 μg/ml concentration. In DPPH free radical scavenging assay, Ph.LO and Ph.FO exhibited IC50 of 20 and 200 μg/ml respectively. The calculated IC50 s were 180 & 60 μg/ml for Ph.LO, and 45 & 50 μg/ml for Ph.FO in scavenging of ABTS and H2 O2 free radicals respectively. Conclusions In the current study, essential oils from leaves and flowers ofP. hydropiper exhibited dose dependent anticholinesterase and antioxidant activities. Leaves essential oil were more effective and can be subjected to furtherin-vitro andin-vivo anti-Alzheimer's studies.